A palavra e a sentença: estudo A palavra e a sentença: estudo introdutório.: A palavra e a sentença: estudo introdutório. - Feitosa Ferreira, Jesus Davi; Da Silva, Adriana Maria; Santos Paula, Aldir (Revista Areia, 2025)
A palavra e a sentença: estudo introdutório.